2021
DOI: 10.3390/jintelligence9030035
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex Invariance of the Woodcock-Johnson IV Tests of Cognitive Abilities: Evidence from Psychometric Network Modeling

Abstract: The Woodcock-Johnson IV Tests of Cognitive Abilities (WJ IV COG) is a comprehensive assessment battery designed to assess broad and narrow cognitive abilities, as defined by the Cattell-Horn-Carroll (CHC) theory of intelligence. Previous studies examined the invariance of the WJ assessments across sex and age groups using factor analytic methods. Psychometric network modeling is an alternative methodology that can address both direct and indirect relationships among the observed variables. In this study, we em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…None have been grounded in the a priori selection of measures as per contemporary CHC or other intelligence theories. These studies have demonstrated that PNA of IQ batteries can produce network results consistent with no- g theoretical models of intelligence (e.g., dynamic mutualism and process overlap) and, when compared with latent variable factor models, the network models identify equally plausible representations of the multidimensional structure of IQ tests ( Bulut et al 2021 ). The PNA models typically identify the same groupings or communities of tests akin to the latent variable common cause factor analysis-based broad CHC score indices (e.g., crystallized intelligence, fluid reasoning, working memory, processing speed in the WAIS-IV; Schmank et al 2021 ).…”
Section: Literature Reviewmentioning
confidence: 80%
See 4 more Smart Citations
“…None have been grounded in the a priori selection of measures as per contemporary CHC or other intelligence theories. These studies have demonstrated that PNA of IQ batteries can produce network results consistent with no- g theoretical models of intelligence (e.g., dynamic mutualism and process overlap) and, when compared with latent variable factor models, the network models identify equally plausible representations of the multidimensional structure of IQ tests ( Bulut et al 2021 ). The PNA models typically identify the same groupings or communities of tests akin to the latent variable common cause factor analysis-based broad CHC score indices (e.g., crystallized intelligence, fluid reasoning, working memory, processing speed in the WAIS-IV; Schmank et al 2021 ).…”
Section: Literature Reviewmentioning
confidence: 80%
“…The final set of 20 broad CHC measures used in the primary analysis, as classified by Schneider ( 2016 ), Schneider and McGrew ( 2018 ), and our own CHC analysis, were: Fluid Reasoning-Gf (Concept Formation, CONFRM; Analysis-Synthesis, ANLSYN), Comprehension–Knowledge-Gc (Oral Vocabulary, ORLVOC, General Information, GENINF; Oral Comprehension, ORLCMP; Verbal Analogies, VRBANL), Visual Processing-Gv (Spatial Relations, VZSPRL; Block Rotation, VZBLKR), Auditory Processing-Ga (Segmentation, SEGMNT; Sound Blending, SNDBLN; Phonological Processing-Word Access, PPACC; Phonological Processing-Word Substitution, PPSUB), Short-term Working Memory-Gwm (Verbal Attention, VRBATN; Objective-Number Sequencing, OBJNUM; Memory for Words, MEMWRD), Retrieval Fluency-Gr (Retrieval Fluency, RETFLU; Phonological Processing–Word Fluency, PPLU), Processing Speed-Gs (Letter–Pattern Matching, LETPAT; Number Pattern Matching, NUMPAT; Pair Cancellation; PAIRCN). It is important to note that this set of WJ IV measures differs from the Bulut et al ( 2021 ) PNA study that was restricted to the primary 14 COG measures in the WJ IV. The current study selected the purest CHC measures from across the WJ IV COG, OL, and ECAD components.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations